Acoustical wave propagation in a cylindrical layer system in viscous medium - Anna GRABOWSKA (Archives of Acoustics)
A problem is considered of an acoustical wave propagating along a hollow infinite elastic cylinder filled with air and surrounded by a viscoelastic tissue. Such a case approximately corresponds to a biopsy performed with the application of a needle introduced to such tissues as liver, kidney, muscles, and the like. In the problem under consideration it was proved, that the volume viscosity is significant, whereas shear viscosity can be neglected. Basic equations were formulated in terms of displacement potentials, as well as the boundary conditions. This led to a characteristic equation of the problem which were solved numerically. It was proved that a boundary wave propagates along the needle with a velocity and attenuation not much smaller than in the surrounding tissue. Part of the energy is transfered from the needle into the tissue where the energy is dissipated. Distributions of the radial and axial stress components and radial displacement components were found.